2016
DOI: 10.1038/npjbcancer.2016.17
|View full text |Cite|
|
Sign up to set email alerts
|

Breast-cancer-specific mortality in patients treated based on the 21-gene assay: a SEER population-based study

Abstract: The 21-gene Recurrence Score assay is validated to predict recurrence risk and chemotherapy benefit in hormone-receptor-positive (HR+) invasive breast cancer. To determine prospective breast-cancer-specific mortality (BCSM) outcomes by baseline Recurrence Score results and clinical covariates, the National Cancer Institute collaborated with Genomic Health and 14 population-based registries in the the Surveillance, Epidemiology, and End Results (SEER) Program to electronically supplement cancer surveillance dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
119
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(142 citation statements)
references
References 30 publications
16
119
0
1
Order By: Relevance
“…Retrospective studies have demonstrated that patients with low RS results are unlikely to respond well to chemotherapy but are more likely to respond to NHT, while higher RS predicts a greater likelihood of a good response to chemotherapy . These results also confirm prior studies showing that patients with a low RS have little to no benefit from chemotherapy, similar to the recently published reports of prospective outcomes in patients with RS less than 11 in the adjuvant setting for both node‐negative and node‐positive patients …”
Section: Discussionsupporting
confidence: 84%
“…Retrospective studies have demonstrated that patients with low RS results are unlikely to respond well to chemotherapy but are more likely to respond to NHT, while higher RS predicts a greater likelihood of a good response to chemotherapy . These results also confirm prior studies showing that patients with a low RS have little to no benefit from chemotherapy, similar to the recently published reports of prospective outcomes in patients with RS less than 11 in the adjuvant setting for both node‐negative and node‐positive patients …”
Section: Discussionsupporting
confidence: 84%
“…Distribution of RS results, in both the N0 and N1 cohort, is consistent with most of the European decision impact studies and postmarketing data in large population datasets , with more than half of the patients presenting with low RS (<18), less than 10% presenting with high RS (>30), and the remainder being classified as intermediate RS (18–30). This distribution differs from original validation studies, in which populations were enriched with patients with higher RS , probably due to different patient selection criteria.…”
Section: Discussionsupporting
confidence: 80%
“…Distant metastases developed in 0.4% of 1406 unselected consecutive patients in this group. Two other studies have reported outcome data in large patient populations treated based on the 21‐gene RS and found a similar incidence of distant recurrence and BC‐specific mortality in patients with a low RS . Only 1 of the 6 patients with distant metastasis in the current study had a tumor with an RS <11.…”
Section: Discussionsupporting
confidence: 59%